The Role of Job Satisfaction in Mediating the Influence of the Work Environment on Organizational Commitment - Cynthia Mahalaksmi, Ni Kadek; Made Suwandana, I Gusti (Jurnal sosial dan sains, 2024)
Background: Companies have the capacity to develop their human resources by fostering employee commitment, necessitating the provision of support to their workforce. Improving the employees' dedication to the organization is closely linked to the environment established by the company. Purpose: The primary objective of this research was to examine how job satisfaction mediates the impact of the work environment on organizational commitment. Method: This research was carried out at PT. Bima Sakti Alterra, involving a sample size of 131 individuals determined through saturation sampling. The data were gathered through interviews and the distribution of questionnaires. The data analysis technique utilized in this research involved path analysis with the application of SPSS.. Results: The findings of this research indicated that the work environment and job satisfaction had a positive and significant impact on organizational commitment. Additionally, the work environment also exhibited a positive and significant influence on job satisfaction. Moreover, job satisfaction served as a mediator in the relationship between the work environment and organizational commitment Conclusion: The theoretical implications of this research support findings from prior research. In practical terms for PT. Bima Sakti Alterra, it involves upholding organizational commitment and establishing a conducive work environment to foster job satisfaction among its employees